PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PERUSAHAAN ENERGI YANG TERDAFTAR DI BEI - Santoso, Juliana Adiningsih; Rohman, Fatchur (Politeknik Negeri Ambon, 2025)
Introduction: Indonesia has great potential in the energy sector, attracting significant investor interest; however, energy companies' financial performance often faces pressures and environmental challenges. The disclosure of environmental, social, and governance (ESG) practices has become increasingly important as a sustainable business strategy, which is believed to enhance corporate value and competitiveness. This study aims to analyze the effect of ESG on the financial performance of energy companies listed on the Indonesia Stock Exchange during the 2020–2023 period.Methods: This research is quantitative in nature. The population studied consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Based on the sampling results, there are 12 energy sector companies as the sample objects. The analytical method used in this research is panel data regression method using E-Views 10 statistical software.Results: Based on the estimation results using panel data regression with the common effect model, it can be concluded that the environmental variable has a significant positive effect on company performance (ROE) with a coefficient of 0.344818 (p-value = 0.0298), and the governance variable also shows a significant positive effect with a coefficient of 0.046795 (p-value = 0.0059). However, the social variable does not significantly affect ROE with a p-value of 0.9748. Keywords: Corporate Performance, Environmental, Governance, Social